Ang paggamit ng mga agham panlipunan sa pagtuturo ng kasaysayan magkakatuwang na larangan, magpapatingkad ng kabuluhan : 2011 annual conference proceedings - Philippine Historical Association Annual Conference (2011 National Historical Commission of the Philippines); National Commission on Culture and the Arts (Philippines); Philippine Historical Association (Quezon City Philippine Historical Association, 2012)
Teaching history in the Philippines; proceedings of a conference.
ISSN 2244-2782"--Verso of title page.
Includes bibliographical references.
Tagalog and English.
Keywords: History -- Study and teaching -- Philippines -- Congresses; Philippines -- History -- Study and teaching -- Congresses